1998
DOI: 10.1029/97gl03187
|View full text |Cite
|
Sign up to set email alerts
|

Suprathermal electrons observed on the TSS‐1R satellite

Abstract: Abstract. Particle measurements up to 27,000 eV were made on the TSS-1R (Tethered Satellite System) satellite. The TSS satellite developed a positive bias due to the Lorentz force. It was the intent that electron measurements on the TSS satellite could be used to track the spacecraft potential and collected current. What was observed was quite different. Accelerated ionospheric electrons were observed to only ~70 eV even though larger spacecraft potentials were observed by other diagnostics on the TSS satellit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1998
1998
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 4 publications
0
9
0
Order By: Relevance
“…Specifically, the TSS-1R results found that as the satellite potential exceeded the ram kinetic energy of O ions (5.3 eV), the level of kilohertz wave activity increased dramatically [26] and a suprathermal electron population appeared at the satellite's surface [27]. The distributions of wave activity and suprathermal electron fluxes were quite nonuniform around the satellite, indicative of both ram and magnetic field limitations to the current collection.…”
Section: B Current Collection Datamentioning
confidence: 96%
“…Specifically, the TSS-1R results found that as the satellite potential exceeded the ram kinetic energy of O ions (5.3 eV), the level of kilohertz wave activity increased dramatically [26] and a suprathermal electron population appeared at the satellite's surface [27]. The distributions of wave activity and suprathermal electron fluxes were quite nonuniform around the satellite, indicative of both ram and magnetic field limitations to the current collection.…”
Section: B Current Collection Datamentioning
confidence: 96%
“…Figure 13 for the space charge atr = 0 (wherer −1 (∂/∂r)r ∂φ/∂r does not vanish) shows the double layer structure peaking before decreasing along the magnetic field. Independently, note that contrary to the case of equation (25), all terms in equation (4 ) and (the left-hand side of) equation (6 ) are comparable. That means that describing transport in our magnetized plasma as a onedimensional problem because cross-field diffusion is much weaker than parallel diffusion is an often used approximation not more valid than in the case of no magnetic field.…”
Section: Figures 1 Andmentioning
confidence: 84%
“…In cold but rarefied, unbounded collisionless space plasmas, probes may be biased highly positive [3], with recent theoretical developments for new applications [4,5]. Ionospheric experiments have found particles heated in the plasma beyond probe [6,7] or spacecraft [8] sheaths.…”
Section: Introductionmentioning
confidence: 99%
“…Particle measurements up to 27 keV were performed on the TSS-1R to track the spacecraft potential and collected current. In addition to the accelerated ionospheric electrons (∼ 70 eV), a suprathermal population of electrons was observed to be centered around 200 eV (Winningham et al, 1998). The authors assumed an AC acceleration of the suprathermal electrons whose free energy is gained from the differential (E × B driven) drift between electrons and ions.…”
Section: Active Experimentsmentioning
confidence: 99%